Availability and use of affordable housing in Austria: How can cheap housing be defined and what are reasonable measures to expand it? - Bacher, Johann; Tamesberger, Dennis (Momentum Quarterly, 2019)
This paper examines how affordable housing can be defined, what the total number of cheap rented apartments in Austria is and which influencing factors there are. For this purpose, a secondary data analysis of the 2017 micro-census is being carried out. In accordance to the concept of the Swiss canton of Lucerne, apartments are being referred to as cheap if their headlease is 70 % lower than the average rent in Austria. The rent burden of the selected households with a net income just over the income limit of the housing benefit results between 21 % and 25.7 %. From a socio-political point of view, the 70 percent threshold represents a very ambitious target. 398.000 apartments that are rented for headlease in Austria – corresponding to 24 % of these apartments - fulfil this criterion. However, only 70.400 of these apartments have been leased in the past three years. An important strategy seems hence not only to build apartments, but above all to increase the proportion of apartments that are rented for headlease when it comes to new buildings or new lettings.
Keywords: affordable housing; cheap housing; micro-census; rents; social policy; Austria